A soil ingestion pilot study for teenage children in China. (July 2018) - Wang, Beibei; Lin, Chunye; Zhang, Xuan; Duan, Xiaoli; Xu, Dongqun; Cheng, Hongguang; Wang, Qin; Liu, Xitao; Ma, Jin; Ma, Junwei; Wu, Fengchang
Abstract: Soil ingestion by people is an important route of exposure to environmental contaminants. Studies on soil ingestion using tracer mass-balance method are mainly for young children and adults, scarcely for teenagers. In such case, the soil ingestion rate for teenagers recommended by regulators is generally identical to that of adults based on one activity pattern modeling study. However, teenagers are expected to have different soil ingestion exposure via ingestion pathway due to different activity patterns and exposure scenarios. We conducted a pilot study on soil ingestion in 30 teenage children aged 12.0–16.5 years from Hubei Province of China, using the best tracer method, with the results compared with previous soil ingestion studies. The estimated mean and median soil ingestion rates for teenagers in this study based on the best five tracers (Al, Ce, Sc, V, and Y) were 45.2 mg d −1 and 44.8 mg d −1 respectively, with the 95% confidence interval of the mean value ranging from 28.0 mg d −1 to 50.9 mg d −1 . These soil ingestion rate estimates were slightly higher than the recommended values for adults by U.S. EPA, but lower than those for Chinese younger children observed in the other similar study. The result in this study is important to access the health risk resulting from exposure to toxic substances in soil via direct soil ingestion pathway by teenagers in China as well as other countries. Graphical abstract: Image Highlights: Soil ingestion rate (SIR) for Chinese teenage children was determined using the best tracer method. The estimated mean and median SIR for Chinese teenage children were 45.2 mg d −1 and 44.8 mg d −1, respectively. The SIR of Chinese teenage children was lower or similar to those for younger children and adults in previous studies.